Effects of limestone filler fineness on the rheological behavior of cement – Limestone filler grouts - Omrane Benjeddou (Elsevier, 2021)
An acceptable viscosity and an easy penetrability of cement - limestone filler grout in the granular matrix of self compacting concrete are an important factors that affecting both its rheological and its hardened properties. This experimental and theoretical work consists to study the effect of limestone filler fineness on the rheological behavior of cement - limestone filler grout. In the first part, five different grouts were prepared by varying the Blaine Specific Surface (BSS) of the limestone filler, 3060, 4750, 6320, 7680 and 9440 cm2/g, respectively. A large number of properties relating to the rheology and the stability are carried out on the five grouts such as grain dispersion, density, volume concentration of solid, dynamic viscosity and Marsh funnel flow. The second part consists to develop a theoretical model to predict the different rheological properties of the grout as function of limestone filler BSS. The results show that the rheological properties of cement-limestone filler grout such as the dispersion percentage, the intergranular distance and the flow time are strongly affected by the limestone fillers fineness. In addition, the experimental and the predicted results present a good agreement.